23Na magnetic resonance imaging-determined tissue sodium in healthy subjects and hypertensive patients - Kopp, Christoph; Linz, Peter; Dahlmann, Anke; Hammon, Matthias; Jantsch, Jonathan; Mueller, Dominik N.; Schmieder, Roland; Cavallaro, Alexander Josef; Eckardt, Kai-Uwe; Uder, Michael; Luft, Friedrich C.; Titze, Jens (Hypertension, 2013)
High dietary salt intake is associated with hypertension; the prevalence of salt-sensitive hypertension increases with age. We hypothesized that tissue Na might accumulate in hypertensive patients and that aging might be accompanied by Na deposition in tissue. We implemented Na magnetic resonance imaging to measure Na content of soft tissues in vivo earlier, but had not studied essential hypertension. We report on a cohort of 56 healthy control men and women, and 57 men and women with essential hypertension. The ages ranged from 22 to 90 years. Na magnetic resonance imaging measurements were made at the level of the calf. We observed age-dependent increases in Na content in muscle in men, whereas muscle Na content did not change with age in women. We estimated water content with conventional MRI and found no age-related increases in muscle water in men, despite remarkable Na accumulation, indicating water-free Na storage in muscle. With increasing age, there was Na deposition in the skin in both women and men; however, skin Na content remained lower in women. Similarly, this sex difference was found in skin water content, which was lower in women than in men. In contrast to muscle, increasing Na content was paralleled with increasing skin water content. When controlled for age, we found that patients with refractory hypertension had increased tissue Na content, compared with normotensive controls. These observations suggest that Na magnetic resonance imaging could have utility in assessing the role of tissue Na storage for cardiovascular morbidity and mortality in longitudinal studies. © 2013 American Heart Association, Inc.
CRIS-Team Scopus Importer:2023-03-08
Keywords: aging; gender difference; hypertension; salt; sodium MRI

Hemodialysis Patients with Cardiovascular Disease Reveal Increased Tissue Na+ Deposition - Friedrich, Anna Carolina; Linz, Peter; Nagel, Armin Michael; Rosenhauer, Daniela; Horn, Stephan; Schiffer, Mario; Uder, Michael; Kopp, Christoph; Dahlmann, Anke (Kidney & Blood Pressure Research, 2022)
BACKGROUND: The relationship between Na+ balance and cardiovascular disease (CVD) in hemodialysis (HD) patients is not yet fully understood. We hypothesized that HD patients co-diagnosed with CVD show increased tissue Na+ accumulation compared to HD patients without CVD. METHODS: In our observational study, 52 HD patients were divided into a group with (23 subjects) or without (29 subjects) a positive history of cardiovascular events. We used 23Na-magnetic resonance imaging (23Na-MRI) at 3.0 Tesla to quantify Na+ content in skin and muscle of both groups directly before and after HD. Additionally, total body fluid distribution was determined by bioimpedance spectroscopy (BIS) and laboratory parameters were assessed. RESULTS: Compared to HD patients without CVD, 23Na-MRI detected an increased Na+ content in skin (21.7 ± 7.3 vs. 30.2 ± 9.8 arbitrary units (a.u.), p < 0.01) and muscle tissue (21.5 ± 3.6 vs. 24.7 ± 6.0 a.u., p < 0.05) in patients with previous CVD events. Simultaneously measured fluid amount by BIS, includingexcess extracellular water (1.8 ± 1.7 vs. 2.2 ± 1.7 L, p = 0.44), was not significantly different between both groups. Tissue Na+ accumulation in HD-CVD patients was paralleled by a higher plasma concentration of the inflammation marker interleukin-6 (5.1, IQR 5.8 vs. 8.5, IQR 7.9 pg/mL, p < 0.05). CONCLUSION: In our cohort, HD patients with CVD showed higher tissue Na+ content than HD patients without CVD, while no difference in body water distribution could be detected between both groups. Our findings provide evidence that the history of a cardiovascular event is associated with disturbances in tissue Na+ content in HD patients.
CRIS-Team Scopus Importer:2022-03-25
Keywords: 23Na-magnetic resonance imaging; Cardiovascular disease; Hemodialysis; Tissue Na+

Interleaved 23Na/1H MRI of the human heart at 7 T using a combined 23Na/1H coil setup and 1H parallel transmission - Ruck, Laurent; Egger, Nico; Wilferth, Tobias; Schirmer, Judith; Gast, Lena; Nagelstraßer, Sophia; Wildenberg, Saskia; Bitz, Andreas; Lanz, Titus; Platt, Tanja; Konstandin, Simon; Kopp, Christoph; et al. (Magnetic Resonance in Medicine, 2025)
Purpose: To evaluate the feasibility of interleaved 23Na/1H cardiac MRI at 7 T using 1H parallel transmission (pTx) pulses. Methods: A combined setup consisting of a 23Na volume coil and two 1H transceiver arrays was employed and the transmit and receive characteristics were compared in vitro with those of the uncombined radiofrequency coils. Furthermore, the implemented interleaved 23Na/1H pTx sequence was validated in phantom measurements and applied to four healthy subjects. For the latter, three customized 1H excitation pulses (universal and individual phase shims (UPS/IPS) and individual 4kT pulses (4kT)) were employed in the interleaved 23Na/1H pTx sequence and compared with the vendor-provided default cardiac phase shim (DPS). Results: Combining both coils resulted in a reduction of the mean 23Na transmit field (B1+) efficiency and 23Na signal-to-noise ratio by 18.9% and 15.4% for the combined setup, whereas the 1H B1+ efficiency was less influenced (−4.7%). Compared with single-nuclear acquisitions, interleaved dual-nuclear 23Na/1H MRI showed negligible influence on 23Na and 1H image quality. For all three customized 1H pTx pulses the B1+ homogeneity was improved (coefficients of variation: CVUPS = 0.30, CVIPS = 0.23, CV4kT = 0.15) and no 1H signal dropouts occurred compared with the vendor-provided default phase shim (CVDPS = 0.37). Conclusion: The incorporation of customized 1H pTx pulses in an interleaved 23Na/1H sequence scheme was successfully demonstrated at 7 T and improvements of the 1H B1+ homogeneity within the heart were shown. Combining interleaved 23Na/1H MRI with 1H pTx is an important tool to enable robust quantification of myocardial tissue sodium concentrations at 7 T within clinically acceptable acquisition times.
CRIS-Team Scopus Importer:2025-04-01
Keywords: 7 Tesla; cardiac sodium (; interleaved acquisition; parallel transmission (pTx)

Modification of Dialysate Na+ Concentration but not Ultrafiltration or Dialysis Treatment Time Affects Tissue Na+ Deposition in Patients on Hemodialysis. - Kopp, Christoph; Kittler, Lukas; Linz, Peter; Kannenkeril, Dennis; Horn, Stephan; Chazot, Charles; Schiffer, Mario; Uder, Michael; Nagel, Armin Michael; Dahlmann, Anke (Kidney International Reports, 2024)
INTRODUCTION: Tissue Na+ overload is present in patients receiving hemodialysis (HD) and is associated with cardiovascular mortality. Strategies to actively modify tissue Na+ amount in these patients by adjusting the HD regimen have not been evaluated. METHODS: In several substudies, including cross-sectional analyses (n = 75 patients on HD), a cohort study and a cross-over interventional study (n = 10 patients each), we assessed the impact of ultrafiltration (UF) volume, prolongation of dialysis treatment time, and modification of dialysate Na+ concentration on tissue Na+ content using 23Na magnetic resonance imaging (23Na-MRI). RESULTS: In the cross-sectional analysis of our patients on HD, differences in dialysate sodium concentration ([Na+]) were associated with changes in tissue Na+ content, whereas neither UF volume nor HD treatment time affected tissue Na+ amount. Skin Na+ content was lower in 17 patients on HD, with dialysate [Na+] of <138 mmol/l compared to 58 patients dialyzing at ≥138 mmol/l (20.7 ± 7.3 vs. 26.0 ± 8.8 arbitrary units [a.u.], P < 0.05). In the cohort study, intraindividual prolongation of HD treatment time was not associated with a reduction in tissue Na+ content. Corresponding to the observational data, intraindividual modification of dialysate [Na+] from 138 to 142 to 135 mmol/l resulted in concordant changes in skin Na+ (24.3 ± 7.6 vs. 26.3 ± 8.0 vs. 20.8 ± 5.6 a.u, P < 0.05 each), whereas no significant change in muscle Na+ occurred. CONCLUSION: Solely adjustment of dialysate [Na+] had a reproducible impact on tissue Na+ content. 23Na-MRI could be utilized to monitor the effectiveness of dialysate [Na+] modifications in randomized-controlled outcome trials.
EVALuna2:568181

Neurometabolic Dysfunction in SPG11 Hereditary Spastic Paraplegia. - Winner, Beate; Marterstock, Dominique; Kopp, Christoph; Dörfler, Arnd; Regensburger, Martin; Krumm, Laura; Schmidt, Manuel; Schmid, Andreas; Spatz, Imke; Marterstock, Dominique; Kopp, Christoph; Kohl, Zacharias; et al. (Nutrients, 2022)
Body composition, adipokine levels, and hypothalamic volume are altered in SPG11. Our data indicate a link between obesity and hypothalamic neurodegeneration in SPG11 and imply that specific metabolic interventions may prevent obesity despite severely impaired mobility in SPG11. Pathogenic variants in SPG11 cause the most common autosomal recessive complicated hereditary spastic paraplegia. Besides the prototypical combination of spastic paraplegia with a thin corpus callosum, obesity has increasingly been reported in this multisystem neurodegenerative disease. However, a detailed analysis of the metabolic state is lacking. In order to characterize metabolic alterations, a cross-sectional analysis was performed comparing SPG11 patients (n = 16) and matched healthy controls (n = 16). We quantified anthropometric parameters, body composition as determined by bioimpedance spectroscopy, and serum metabolic biomarkers, and we measured hypothalamic volume by high-field MRI. Compared to healthy controls, SPG11 patients exhibited profound changes in body composition, characterized by increased fat tissue index, decreased lean tissue index, and decreased muscle mass. The presence of lymphedema correlated with increased extracellular fluid. The serum levels of the adipokines leptin, resistin, and progranulin were significantly altered in SPG11 while adiponectin and C1q/TNF-related protein 3 (CTRP-3) were unchanged. MRI volumetry revealed a decreased hypothalamic volume in SPG11 patients. CONCLUSIONS BACKGROUND METHODS RESULTS
Keywords: SPG11; adipokines; bioimpedance spectroscopy; hypothalamus; leptin; obesity

Reduction of Tissue Na+ Accumulation After Renal Transplantation - Dahlmann, Anke; Linz, Peter; Zucker, Isabelle; Haag, Viktor; Jantsch, Jonathan; Dienemann, Thomas; Nagel, Armin Michael; Neubert, Patrick; Rosenhauer, Daniela; Rauh, Manfred; Horn, Stephan; Müller, Dominik N.; et al. (Kidney International Reports, 2021)
Introduction: Chronic kidney disease (CKD) engenders salt-sensitive hypertension. Whether or not tissue Nathorn accumulation is increased in CKD patients remains uncertain. How tissue Nathorn is affected after renal transplantation has not been assessed.
CRIS-Team WoS Importer:2021-10-01

Sodium quantification in skeletal muscle: comparison between Cartesian gradient-echo and radial ultra-short echo time 23Na MRI techniques - Gerhalter, Teresa; Schilling, Felix; Zeitouni, Nour; Linz, Peter; Baudin, Pierre Yves; Kannenkeril, Dennis; Kopp, Christoph; Dahlmann, Anke; Schmieder, Roland; Uder, Michael; Nagel, Armin Michael; Gast, Lena (European Radiology Experimental, 2024)
Background: Clinical magnetic resonance imaging (MRI) studies often use Cartesian gradient-echo (GRE) sequences with 2-ms echo times (TEs) to monitor apparent total sodium concentration (aTSC). We compared Cartesian GRE and ultra-short echo time three-dimensional (3D) radial-readout sequences for measuring skeletal muscle aTSC. Methods: We retrospectively evaluated 211 datasets from 112 volunteers aged 62.3 ± 12.1 years (mean ± standard deviation), acquired at 3 T from the lower leg. For 23Na MRI acquisitions, we used a two-dimensional Cartesian GRE sequence and a density-adapted 3D radial readout sequence with cuboid field-of-view (DA-3D-RAD-C). We calibrated the 23Na MR signal using reference tubes either with or without agarose and subsequently performed a relaxation correction. Additionally, we employed a six-echo 1H GRE sequence and a multi-echo spin-echo sequence to calculate proton density fat fraction (PDFF) and water T2. Paired Wilcoxon signed-rank test, Cohen dz for paired samples, and Spearman correlation were used. Results: Relaxation correction effectively reduced the differences in muscle aTSC between the two acquisition and calibration methods (DA-3D-RAD-C using NaCl/agarose references: 20.05 versus 19.14 mM; dz = 0.395; Cartesian GRE using NaCl/agarose references: 19.50 versus 18.82 mM; dz = 0.427). Both aTSC of the DA-3D-RAD-C and Cartesian GRE acquisitions showed a small but significant correlation with PDFF as well as with water T2. Conclusions: Different 23Na MRI acquisition and calibration approaches affect aTSC values. Applying relaxation correction is advised to minimize the impact of sequence parameters on quantification, and considering additional fat correction is advisable for patients with increased fat fractions. Relevance statement: This study highlights relaxation correction’s role in improving sodium MRI accuracy, paving the way for better disease assessment and comparability of measured sodium signal in patients. Key points: • Differences in MRI acquisition methods hamper the comparability of sodium MRI measurements. • Measured sodium values depend on used MRI sequences and calibration method. • Relaxation correction during postprocessing mitigates these discrepancies. • Thus, relaxation correction enhances accuracy of sodium MRI, aiding its clinical use. Graphical Abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-05-31
Keywords: Calibration; Magnetic resonance imaging; Muscle (skeletal); Sodium; Volunteers

The Delay of Recanalisation of Acutely Thrombosed Dialysis Arteriovenous Access Until the Next Workday has No Negative Impact on Clinical Outcome - Hellwig, Konstantin; Zicha, Stefan; Kopp, Christoph; Rother, Ulrich; Papatheodorou, Nikolaos; Uder, Michael; Schmid, Axel (Cardiovascular and Interventional Radiology, 2024)
Purpose: The necessity of providing endovascular recanalization of acutely thrombosed arteriovenous access (AV access) during weekend is questionable, since hemodialysis can alternatively be achieved by temporarily placed non-tunneled central venous catheters (CVC). Interventional therapy of acutely thrombosed AV access is provided only on weekdays in the study center. This study aimed to compare outcomes in patients admitted on weekdays and on the weekend. Methods: A total of 355 endovascular procedures for thrombosed AV access performed in a single tertiary center from 2007 to 2017 were retrospectively analyzed for technical and clinical success, complications, rate of CVC and length of hospitalization. Technical success was defined as adequate blood flow with less than 30% residual stenosis, clinical success was defined as at least one successful hemodialysis after recanalization. There were two groups: patients who had to wait at least 2 days for recanalization due to admission at the weekend (n = 59, at-the-weekend group, ATW group) and patients receiving therapy no later than the day after admission (n = 296, on a working day group, OAW group). Results: The technical/clinical success rate was 96.6%/88.1% in the ATW and 89.1%/84.6% in the OAW group (p >.05). Complications did not differ among groups (p >.05). Despite a higher rate of CVC, no attributed additional adverse events or complications were observed in the ATW group (p >.05). Conclusion: Despite a longer time until treatment and a higher rate of short-term CVC, it seems to be justified to provide recanalization of dialysis shunts only during weekdays. Graphical Abstract: (Figure presented.)
CRIS-Team Scopus Importer:2025-02-04
Keywords: Arteriovenous fistula; Endovascular; Hemodialysis; Recanalization; Thrombosis

Tissue sodium content correlates with hypertrophic vascular remodeling in type 2 diabetes - Kannenkeril, Dennis; Jung, Susanne; Harazny, Joanna; Striepe, Kristina; Ott, Christian; Dahlmann, Anke; Kopp, Christoph; Schiffer, Mario; Linz, Peter; Nagel, Armin Michael; Uder, Michael; Schmieder, Roland (Journal of Diabetes and Its Complications, 2021)
Background: Prospective studies describe a linkage between increased sodium intake and higher incidence of cardiovascular organ damage and end points. We analyzed whether tissue sodium content in the skin and muscles correlate with vascular hypertrophic remodeling, a risk factor for cardiovascular disease.
CRIS-Team WoS Importer:2021-12-03

Vitamin K1 and progression of cardiovascular calcifications in hemodialysis patients: the VitaVasK randomized controlled trial - Saritas, Turgay; Reinartz, Sebastian; Krueger, Thilo; Ketteler, Markus; Liangos, Orfeas; Labriola, Laura; Stenvinkel, Peter; Kopp, Christoph; Westenfeld, Ralf; Evenepoel, Pieter; Siepmann, Robert; Wied, Stephanie; et al. (Clinical Kidney Journal, 2022)
Lay Summary Patients on chronic dialysis exhibit extensive cardiovascular calcifications and vitamin K deficiency. The vitamin K-dependent matrix Gla protein (MGP) is a potent inhibitor of vascular calcification. The multicentre, randomized, open-label, controlled VitaVasK trial showed marked attenuation of cardiovascular calcification progression in chronic haemodialysis patients treated with vitamin K1. Vitamin K1 supplementation greatly increased the serum vitamin K concentration and reduced inactive MGP levels. The treatment was safe, as no adverse advents were noted. Larger randomized controlled trials are needed to confirm vitamin K1 therapy as a safe, potent and cost-effective treatment option to reduce the progression of vascular calcification in haemodialysis patients.
CRIS-Team WoS Importer:2022-09-23